Case Discussion Learning Method in Improving Knowledge About the Differences Between Menstruation and Istihadzoh in New Students of Assalafiat 2 Islamic Boarding School - Dian Dinarni; Nurhaemin Nurhaemin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
The background of this study was found to see new students whose possible understanding of the science of menstruation is still minimal. This knowledge will be directly related to the continuity of worship. The purpose of this study is to determine the level of knowledge about the differences between menstruation and istihadzoh in new students of Pondok pesantren Assalafiat 2. The research method used is qualitative with a case study approach. Data collection techniques in this study used discussions, interviews, and documentation. The Data were obtained through a discussion conducted at one of the activities at the Assalafiat 2 Islamic boarding school which takes place once a week, namely the schedule of reciting (learning) mahid science, interview activities with new students were also assisted by the Islamic boarding school board. Data analysis techniques used in this study are data reduction, data display, and conclusion. The results of the study using the case study method to improve the understanding of new students about menstruation and istihadzoh in Pondok pesantren Assalafiat 2 can be considered successful. With this method, students also learn to express their opinions and train their focus to be able to digest what is being discussed.